A Bilingual Approach to Islamic Studies Education for Upper Primary Students in Malaysian International Islamic Schools - Tahir, Syeda Rabia (2023)
Many international Islamic schools in Malaysia enroll learners from various multicultural and multilingual backgrounds. In these schools, proficiency in both Arabic and the language of instruction, typically English, is required for Islamic education. However, many students encounter difficulties because of limited proficiency in these two languages. Thus, it is crucial to examine how the teaching and learning (T&L) of Islamic studies (IS) is conducted in international Islamic schools. This study aimed to answer the following research questions: a) What is the nature of the curriculum of IS in international Islamic schools?; b) What bilingual teaching and learning methods are employed for IS in international Islamic schools? ; c) How is the assessment of IS conducted in international Islamic schools? ; d) What challenges are faced by stakeholders in learning IS in a bilingual environment? ; and e) What are the perceptions of stakeholders regarding the bilingual education of IS in international Islamic schools? The study adopted a mixed-method, sequential explanatory research design which involved the use of questionnaires and interview protocols. The participants of the study were from seven international Islamic schools in Selangor and Kuala Lumpur, Malaysia, including principals/heads of department, teachers, students and parents (n=449). A purposeful sample of 54 participants was selected for stakeholder interviews. The results of the study revealed that: a) the curriculum appears to emphasise the inculcation and practice of Islamic philosophy, teacher and student- centered T&L as well as bilingual practices; b) T&L involves use of Arabic and English with a focus on the application of Islamic values; c) an emphasis on summative assessment, with English as the language of assessment; d) the use of two languages in T&L is a major challenge for teachers and learners; e) all stakeholders view the practice of bilingual education for the Islamic studies subject positively. This research contributes to our understanding of T&L as well as effective classroom communication by : a) highlighting the benefits of a bilingual approach to IS within multicultural and multilingual school communities; b) expanding the discourse in the interdependence of Arabic and English in mediating meaning during IS lessons; c) deepening knowledge on instructional policies in relation to language integration in the classroom, as well as challenges in the use of a bilingual approach to IS instruction; and d) providing insight to teachers’ role and competencies in implementing IS lessons, and how they are related to teacher professional development.